Epigenetic Mechanisms Governing Innate Inflammatory Responses - Perkins, Darren J. (J Interferon Cytokine Res, 2016)
Toll-like receptors (TLRs) are major receptors of the host innate immune system that recognize conserved pathogen-associated molecular patterns (PAMPs) of invading microbes. Activation of TLR signaling culminates in the expression of multiple genes in a coordinate and kinetically defined manner. In this review, we summarize the current studies describing the chromatin landscape of TLR-responsive inflammatory genes and how changes to this chromatin landscape govern cell type-specific and temporal gene expression. We further elaborate classical endotoxin tolerance and epigenetic mechanisms controlling tolerance and interferon priming effects on inflammatory promoters.